Correction: Trypanosoma cruzi-specific IFN-γ-producing cells in chronic Chagas disease associate with a functional IL-7/IL-7R axis. - María A Natale; Gonzalo Cesar; Maria G Alvarez; Melisa D Castro Eiro; Bruno Lococo; Graciela Bertocchi; María C Albareda; Susana A Laucella (Public Library of Science (PLoS), 2019)
[This corrects the article DOI: 10.1371/journal.pntd.0006998.].